Peran Alat dan Media Pembelajaran dalam Studi Hadist Tarbawi: Strategi Efektif untuk Meningkatkan Pemahaman dan Implementasi Nilai-Nilai Pendidikan Islam - Farida Nurul Khasanah; Wassim Ahmad Fahrudin; Imam Anas Hadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study intends to examine the role of learning tools and media sourced from the hadith tarbawi, and to explain strategies that are considered effective in improving understanding and implementation of Islamic education values. The method used is qualitative library research. The source of this data is the hadith on learning methods and various literature which related to the object of research. The data collection technique uses the library research method, namely a data collection technique that is not directly aimed at the research subject, but through several Al-Qur'an and Al-Hadith, books, magazines, and other documentary materials that are most relevant to the study. From this study, it can be concluded that the learning tools and media used by the Prophet, contained in several sources of hadith, can be applied in today's learning. These tools and media are considered very ideal to be applied and implemented in the Islamic learning process. However, adjustments and developments are needed to be more effective in improving understanding of Islamic education values ​​and their implementation. Keywords: Educational Hadith, Learning Media, Islamic Learning Strategies